Adult rhabdomyoma presenting as thyroid nodule on fine‐needle aspiration in patient with Birt‐Hogg‐Dubé syndrome: Case report and literature review. Issue 6 (18th March 2020) - Black, Margaret; Wei, Xiao‐Jun; Sun, Wei; Simms, Anthony; Negron, Raquel; Hagiwara, Mari; Chidakel, Aaron R.; Hodak, Steven; Persky, Mark S.; Shi, Yan
Abstract: Extracardiac rhabdomyoma is an uncommon benign striated muscle tumor with a predilection for the head and neck region. However, it is extremely rare for extracardiac rhabdomyoma to present as a thyroid nodule. We report a case of rhabdomyoma diagnosed by thyroid fine‐needle aspiration (FNA) in a patient with Birt‐Hogg‐Dubé (BHD) syndrome. A 60‐year‐old man with BHD syndrome presented for recurrent pneumothorax. Chest CT incidentally identified a thyroid nodule. Subsequent sonography confirmed a 4.44 × 2.28 × 2.82 cm solid, hypoechoic nodule with smooth margins in the right upper pole. Ultrasound‐guided FNA revealed many clusters and scattered isolated large polygonal cells with abundant granular cytoplasm and small peripherally located nuclei. Vague striations in the cytoplasm were focally identified. No follicular cells or colloid was present. Immunocytochemistry on one direct smear slide demonstrated diffuse positivity for desmin, supporting muscular differentiation. Subsequent surgery identified an adult rhabdomyoma originating from the inferior constrictor muscle of the neck and anteriorly displacing the thyroid. Because the mass was intimately associated with the thyroid gland, it was initially mistaken for a thyroid nodule on ultrasound. Diagnosis of rhabdomyoma on FNA is challenging, especially when rhabdomyoma mimics a thyroid nodule on imaging. The differential diagnosis includes Hurthle cell neoplasm, granular cell tumor, colloid nodule, and normal striated skeletal muscle. Adequate radiologic data and familiarity with the cytologic features of rhabdomyoma are critical for an accurate diagnosis.